Angiotensin II receptor blockers improve peripheral endothelial function: a meta-analysis of randomized controlled trials. - Shuang Li (Public Library of Science (PLoS), 2014)
Objective(s) Several studies have assessed the effect of angiotensin II receptor blockers (ARBs) on peripheral endothelial dysfunction as measured by flow-mediated vasodilatation (FMD), a widely-used indicator for endothelial function. We conducted a meta-analysis to investigate the effect in comparison to placebo or no treatment and other antihypertensives. Methods MEDLINE, Cochrane library and EMBASE were searched to September 2013 for randomized controlled trials (RCTs) that assessed the effect of ARBs versus placebo or no treatment and other antihypertensives (angiotensin-converting enzyme inhibitors (ACEIs), calcium channel blockers (CCBs), β-blockers, diuretics) by forearm FMD. Furthermore, we also use meta-regression to analyze the relationship between the endothelial function and the duration of ARBs treatments. Results In 11 trials including 590 patients, ARBs (n = 315) significantly improved FMD (1.36%, 95% confidence internal [CI]:1.28 to 1.44) versus placebo or no treatment (n = 275). In 16 trials that included 1028 patients, ARBs (n = 486) had a significant effect (0.59%, 95% CI: 0.25 to 0.94) on FMD when compared with other antihypertensives (n = 542). In 8 trials, ARBs (n = 174) had no significant effect (-0.14%, 95% CI: -0.32 to 0.03) compared with ACEI (n = 173). Compared with others, the benefits of ARBs, respectively, were 1.67% (95% CI: 0.65 to 0.93) in 7 trials with CCBs, 0.79% (95% CI: 0.42 to 1.01) with β-blockers in 3 trials and 0.9% (95% CI: 0.77 to 1.03) with diuretics in 3 trials. Importantly, we found ARBs were less effective in a long time span (95% CI: -1.990 to -0.622) than the first 6 months (95% CI: -0.484 to 0.360). Conclusions This study shows that ARBs improve peripheral endothelial function and are superior to CCBs, β-blockers and diuretics. However, the effect couldn't be maintained for a long time. In addition, there was no significant difference between ARBs and ACEI.